PENGETAHUAN DAN DUKUNGAN KELUARGA TERHADAP PELAKSANAAN INISIASI MENYUSU DINI DI POSKESDES DESA BUMI SERDANG KEC TUNGKAL ILIR KABUPATEN BANYUASIN TAHUN 2022 - Ratna Dewi (KOLONI, 2022)
Early Breastfeeding Initiation is one of the government programs in the health sector in an effort to reduce infant mortality (IMR) by giving exclusive breastfeeding to newborns up to six months of age, through the application of IMD during childbirth, namely prohibiting placing the baby on the mother's chest so that the baby can looking for his own mother put. WHO recommends IMD, which is an act of laying the baby on the mother's chest immediately after birth with the skin to skin method, the baby's head is placed between the mother's two breasts then letting the baby use it alone to find the mother's nipple. The purpose of knowing the relationship of knowledge and family support to the implementation of early breastfeeding initiation in postpartum mothers. This type of analytic survey research with a cross sectional approach with accidental sampling method. The research sample is 16 respondents. The research results obtained from 16 respondents, there were 10 respondents (62.5%) who carried out IMD and 4 respondents (37.5%) did not carry out IMD. There were 11 respondents (68.8%) who had good knowledge and 5 respondents (31.2%) who had less knowledge. There were 9 respondents (56.2%) who received family support and 7 respondents (343.8%) did not receive family support. The results of the chi-square statistical test found that there was a relationship between knowledge of the implementation of IMD with a p value = 0.036 < ∂ : 0.05 and there was no relationship between family support and the implementation of IMD with a p value = 0.035 > ∂ : 0.05. It is hoped that counseling can be carried out regarding the implementation of IMD directly to mothers since pregnancy so that mothers understand the importance of carrying out IMD immediately after delivery. Keywords: Knowledge, Family support, Early initiation of breastfeeding